PP1A Modulates the Efficacy of Lenvatinib Plus ICIs Therapy by Inhibiting Ferroptosis in Hepatocellular Carcinoma - Jitong Zhou; Meng Gao; Shikun Zhang; Wing‐Wa Guo; Wenzhi He; Minghe Zhang; Xi Chen; Cairang Dongzhi; Xiaomian Li; Yufeng Yuan; Weijie Ma (Advanced Science, 2025)
Abstract Advanced hepatocellular carcinoma (HCC) is characterized by poor prognosis, primarily due to limited therapeutic options and resistance to treatment. Although the combination of tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) has shown promising potential, the underlying mechanisms remain inadequately understood. Here, serine/threonine‐specific protein phosphatase (PP1A) is upregulated in Lenvatinib‐resistant HCC cells and correlates with poor prognosis. Functional experiments revealed that PP1A promotes HCC progression both in vitro and in vivo. Transcriptomic analysis and ferroptosis metabolite profiling (e.g., ROS, Fe2⁺, lipid‐ROS, and GSH) demonstrated that PP1A inhibits Lenvatinib‐induced ferroptosis by dephosphorylating Keap1 at site 104. This disruption of the Keap1‐Nrf2 interaction enhances the transcription of ferroptosis‐related markers and immune checkpoint PD‐L1. Notably, single‐cell sequencing and co‐culture experiments revealed that PP1A knockdown alleviates T cell exhaustion and immune evasion, thereby improving antitumor immunity. In vivo experiments further demonstrated that PP1A knockdown significantly enhances the efficacy of Lenvatinib‐ICIs combination therapy. Overall, our findings highlight PP1A as a critical regulator of ferroptosis and antitumor immunity, suggesting its potential as a predictive biomarker and therapeutic target for improving outcomes in advanced HCC.